Distribution and the resources of Sea Holly (Eryngium maritimum L.) on the western shore of the Gulf of Gdańsk - Żółkoś, Katarzyna; Afranowicz, Renata; Bloch-Orłowska, Joanna; Kozieł, Kamila (Biodiversity: Research and Conservation, 2007)
Studies on the distribution of Sea Holly were carried out in summer 2006 along a 150 km stretch of the western shore of the Gulf of Gdańsk, between Władysławowo and Świbno, including the Hel Peninsula. Besides our own research, all available historical and contemporary literature was analyzed to reconstruct changes of Sea Holly distribution that have taken place in the studied area since 1848. During the field research altogether 6480 individuals of Eryngium maritimum L. were found and 53% of them grew on a 2 km long section of the shore between Rewa and Mechelinki. Other populations of the species were observed on the Sobieszewo Island, the Hel Peninsula, between Westerplatte and Górki Zachodnie and in Babie Doły. The greatest changes in Sea Holly distribution during the last 160 years have taken place at the base and in the middle part of the Hel Peninsula and from Mechelinki to Gdańsk. Vanishing of the species populations was mostly a consequence of transformations of coastal habitats, related to the development of towns and ports as well as to increasing tourist pressure. The results of investigations point out at an urgent need for monitoring and protection of the existing populations of Eryngium maritimum. At present, only one locality is under the law protection as a nature reserve (‘Mechelińskie Łąki’), but even this one is highly threatened by tourist pressure. Hitherto protection of Sea Holly is insufficient and should be extended to the protection of all habitats suitable for the species.